Possibilities of targeted therapy for myelofibrosis: Moscow experience - O. Yu. Vinogradova; M. M. Pankrashkina; D. I. Shikhbabaeva; M. V. Chernikov; A. L. Neverova; V. L. Ivanova; E. A. Nikitin; E. V. Usikova; V. V. Ptushkin (Онкогематология)
Background. For many years the primary aim of treatment strategy for ph-negative myeloproliferative neoplasms has been to restrain disease progression, with lasting relief and management of symptoms to improve patients’ quality of life. Generally, this did not lead to a significant increase in life expectancy with primary myelofibrosis and didn’t decrease the risk of fibrosis in patients with polycythemia vera and essential thrombocythemia. To date a new class of targeted drugs has been developed, it is JAK2 inhibitors with pathogenetic effects. The results of clinical trials showed the high efficacy of the first registered drug of this its kind – ruxolitinib – that includes a faster reduction in the symptoms of tumor intoxication and in symptoms associated with the development of splenomegaly and increase in the overall survival rates. It is known that the data obtained during clinical trials of medicines may differ from the results obtained in routine clinical practice. In actual practice drugs are used in a much wider heterogeneous population of patients, less limited first of all by age and comorbid characteristics. It is possible to analyze cohorts of patients including a larger number of clinical cases with a longer follow-up period. In this regard of great interest is the actual clinical experience of long-term use of ruxolitinib in patients whose set is limited only by clinical contraindications for prescribing the drug.Aim. To present our own actual experience of targeted therapy of myelofibrosis and compare the results obtained with the data of clinical trials.Materials and methods. Our analysis includes data from 141 patients (67 (47.5 %) men and 74 (52.5 %) women) in a chronic phase myelofibrosis. All patients received ruxolitinib. Of these, 109 (69 %) patients had primary myelofibrosis, 26 (16 %) – postpolycythemia myelofibrosis, 6 (4 %) – postessential thrombocythemia myelofibrosis. The median age at the start of therapy was 62 (18–84) years. The median disease duration before ruxolitinib was prescribed – 79 (1–401) months. According to the dIpSS (dynamic International prognostic Scoring System) criteria, 13 % of patients were assigned to the low risk group, 38 % – to the intermediate-1, 36 % – to the intermediate-2, 13 % – to the high risk group. Most patients (52 %) had grade 3 bone marrow fibrosis.Results. The median duration of treatment was 18 (range from 1 to 115) months. Symptoms of intoxication were relieved 74 (81 %) of 91 patients, the spleen size decreased in 81 % of patients (the spleen size returned to normal in 25 % of patients). The increase in the median hemoglobin level was 15 %. The proportion of patients requiring blood transfusion decreased by 4 times (from 39 to 9 %). Mean platelet levels normalized in most patients with baseline high and low platelet levels. A complete clinical and hematological response was achieved in 16 % (n = 23) of cases, a partial response – in 26 % (n = 37) of cases, clinical improvement – in 21 % (n = 30), disease stabilization – in 33 % (n = 46) of cases. No response was received in 1 (1 %) patient and in 3 (3 %) cases there was progression of the disease. At the time of analysis, 81 (57 %) of 141 patients were continuing the ruxolitinib treatment. The fatal outcome in 33 (22 %) patients was associated with concomitant diseases, among which 20 (14 %) died from proven COvId-19 infection. Overall survival: 1-year 81 %, 2-year 73 %, 5-year 50 %. Overall survival excluding deaths due to COvId-19: 1-year 92 %, 2-year 85 %, 5-year 70 %. Massive splenomegaly and a high degree of fibrosis were unfavorable predictors of prognosis of overall survival.Conclusion. Target therapy with Janus kinase inhibitor ruxolitinib has demonstrated high efficacy in patients with myelofibrosis in routine clinical practice. The most rapid effect ruxolitinib had on the spleen size and the symptoms of intoxication. Tolerability of ruxolitinib therapy was generally satisfactory. The overall and progression-free survival rates in patients with myelofibrosis, receiving ruxolitinib in the clinical setting was consistent with the results of international multicenter clinical trials.